Bank Efficiency and Non-Performing Financing (NPF) in the Indonesian Islamic Banks - Havidz, Shinta Amalina Hazrati; Setiawan, Chandra (Asian Journal of Economic Modelling, 2015)
This paper investigates the efficiency of Indonesian Islamic Banks by employing Data Envelopment Analysis (DEA) approach, the determinants of banks efficiency and non-performing financing (NPF). The authors further examine the inter-temporal relationships between bank efficiency and non-performing financing (NPF) of Indonesian Islamic Banks to test two hypotheses: ‘Bad Luck’ and ‘Bad Management’. The data covers the periods of January 2008 – September 2014 using quarterly-published report data from Central Bank (Bank Indonesia) with 4 Islamic banks as the sample of research. The bank efficiency is measured by data envelopment analysis (DEA) estimating overall technical efficiency (OTE), pure technical efficiency (PTE), and scale efficiency (SE). Panel Least Square for fixed effect model is used to find the determinants of efficiency and NPF. Panel-VAR model is used to test the two hypotheses ‘Bad Luck’ and ‘Bad Management’. The finding reveals that none of the Islamic banks consistently efficient for all periods of research by OTE, PTE, and SE. The overall results show that efficiency of Islamic Banks is affected significantly by return on assets (ROA), operational efficiency ratio (OER), and inflation rates (INF), while financing to deposit ratio (FDR), capital adequacy ratio (CAR), size, and GDP growth rate have insignificant effect on bank efficiency. Regarding the determinants of NPF, there are significant effects of size, operational efficiency ratio (OER), and GDP growth rate toward NPF, while return on assets (ROA), financing to deposit ratio (FDR), capital adequacy ratio (CAR), and inflation rate (INF) have insignificant effect on NPF. The research supports “Bad Management” hypothesis since it reveals that possibly because of poor financing portfolio management of Indonesian Islamic Banks in the period and sample of the research.